Analysis of Development and Changes in Reading Interests Using Online Libraries - Nisa, Alifa Kholidatu (Edulib, 2023)
The problem often faced by people in Indonesia is the decreasing level of public interest in reading information. This information is obtained from various sources, one of which is from libraries. In the current digital era, the development and changes in reading interest have begun to shift from regular libraries to digital libraries or what are often called Online Libraries. Digital libraries are quite flexible and provide many conveniences to their users. This study uses a quantitative method with a descriptive approach. This study aims to analyze the development and changes in reading interest using digital libraries or Online Libraries. The results of this study indicate the influence of digital libraries on the level of reading interest. If the number of digital libraries increases, there will be a decrease in reading interest. Likewise, if the number of libraries decreases, there will be an increase in reading interest